Promotional tools influence customerbased brand equity of Adabi in Selangor / Hazirah Ismailuddin - Ismailuddin, Hazirah (Faculty of Business and Management, 2008)
The main purpose of the study is to examine the promotional tools that affect customerbased brand equity of Adabi brand. A total of 100 questionnaires have been distributed to customers of Adabi who reside in Selangor by using cluster sampling. The data was analyzed and the result showed that advertisement, free sample and sponsorship which are the promotional tool that Adabi customers in Selangor more familiar with do have significant relationship with customer-based brand equity. The strongest equity of Adabi brand is performance of Adabi brand besides the positive feeling of customers toward Adabi brand. Advertisement is resulted as the most influential tools that can change the brand equity beside another tool, free sample. Another finding is certain demographic factors do have significant relationship with customer-based brand equity which is age, working sector and monthly household income.